Age 23 years + oral health questionnaire in Avon Longitudinal Study of Parents and Children - Dudding, Tom; Haworth, Simon; Sandy, Jonathan; Timpson, Nicholas J. (Wellcome open research, 2018)
Oral health data in large longitudinal cohort studies is rarely collected at multiple time-points. This type of data is important for assessing oral health trajectories and their determinants. This data resource includes self-report questionnaire data on up to 4,222 young adults at approximately 23 years of age from the Avon Longitudinal Study of Parents and Children (ALSPAC). The resource includes questions on dental attendance, tooth restorations and extractions, third molars (wisdom teeth) and mouth ulcers. This round of data collection follows on from similar questionnaires at ages 7, 10 and 17 years. The ALSPAC study provides an opportunity to combine this oral health data with extensive phenotype, genetic, epigenetic and metabolomic data from the participants, their mothers and fathers.